Genomic analysis of Plasmodium falciparum isolates across different altitudinal zones along the slope of Mount Cameroon - Apinjoh, Tobias O.; Ajonina, Marcelus U.; Abera, Deriba; Chi, Hanesh F.; Tata, Roland B.; Mugri, Regina N.; Golassa, Lemu; Achidi, Eric A.; Amambua-Ngwa, Alfred (Frontiers in Malaria, 2023)
Background Malaria elimination is threatened by the emergence and rapid spread of drug resistance. Understanding the demographic history of Plasmodium falciparum and the genetic basis of adaptation to antimalarial treatment and host immunity is critical to elimination efforts. This study sought to characterize the diversity of P. falciparum isolates across different altitudes along the slope of Mount Cameroon. Methodology Using the Illumina next-generation sequencing platform P. falciparum isolates from low, intermediate and high altitudes along the slope of Mount Cameroon were studied to determine their genetic diversity, population structures, and signatures of selection in known drug resistance alleles. Results A total of 77,253 single-nucleotide polymorphisms were identified from 220 quality P. falciparum clinical isolates from high (24,214), intermediate (24,426), and low (28,613) altitude. About 49%, 48.2% and 30% of the parasite isolates from high, intermediate, and low altitudes, respectively had FWS values > 0.95 indicative of dominant mixed genotype infections and low population sub-structure with high potential for out-crossing. No significant difference was observed in within-host diversity while population structure analysis did not separate the isolates in the three major altitudinal groups by PCA, FST and admixtures, suggesting bidirectional gene flow among the populations. A total of 94 antigenic genes under balancing selection were detected in the area including vaccine candidate gene ama1, eba175, msp1, trap, dblmsp, and clag2. Moreover, 17 of these genes were identified to be under both recent positive directional and positive balancing selection including the prominent host immune target genes surfin 8.2, trap, and ama1. Recent directional selection analysis using integrated standardized haplotype score (iHS) did not detect any selection signatures in the Pfdhfr, Pfdhps, Pfmdr1, and PfK13 genes. Furthermore, no PfKelch13 validated mutation associated with artemisinin resistance was identified in this study and no structural divergence was noticed among the P. falciparum parasite populations across different altitudes around the Mount Cameroon region. Discussion Findings revealed high genetic diversity and low population structure suggesting that malaria transmission remain high in the study area and parasite populations circulating around the slope of Mount Cameroon are homogenous.